The COVID-19 Crisis: New Sociologies and Feminisms - Batthyány, Karina (2021)
For the social sciences, the main novelty that the mega-crisis linked to the expansion of COVID-19 has produced is the recognition of the impossibility of ignoring that we live in territorial societies that are increasingly globally interdependent. If, before 2020, social studies were still able to develop acceptable justifications for dispensing with a global framework of observation, this is no longer the case. The pandemic started a process of irreversible attention, which will sooner or later affect all research objects, and from which there is no turning back.It is no longer possible to omit the existence of a global society without falling into serious anachronisms. If, in the times of maritime navigation, the conquest of America initiated material globalization, it is likely that the blows dealt by the representations of COVID-19 on our digital screens will once and for all anchor globalization as intellectual common sense. Thus, rather than expanding the process of material globalization, the collective processing of the avatars of COVID-19 is expanding the process of mental globalization. We are not witnessing the decline of micro-social sensibilities and subjective singularizations, but rather a vertical, abrupt, unthinkable end to a long process of ignorance and historical denial of the gravitational forces of world dynamics on societies.